The effect of electromyographic feedback functional electrical stimulation on the plantar pressure in stroke patients with foot drop - Li, Xiaoting; Li, Hanting; Liu, Yu; Liang, Weidi; Zhang, Lixin; Zhou, Fenghua; Zhang, Zhiqiang; Yuan, Xiangnan (Frontiers in Neuroscience, 2024)
The purpose of this study was to observe, using Footscan analysis, the effect of electromyographic feedback functional electrical stimulation (FES) on the changes in the plantar pressure of drop foot patients.This case-control study enrolled thirty-four stroke patients with foot drop. There were 17 cases received FES for 20 min per day, 5 days per week for 4 weeks (the FES group) and the other 17 cases only received basic rehabilitations (the control group). Before and after 4 weeks, the walking speed, spatiotemporal parameters and plantar pressure were measured.Results: After 4 weeks treatments, Both the FES and control groups had increased walking speed and single stance phase percentage, decreased step length symmetry index (SI), double stance phase percentage and start time of the heel after 4 weeks (p<0.05). The increase in walking speed and decrease in step length SI in the FES group were more significant than the control group after 4 weeks (p<0.05). The FES group had an increased initial contact phase, decreased SI of the maximal force (Max F) and impulse in the medial heel after 4 weeks (p<0.05).The advantages of FES were: the improvement of gait speed, step length SI, and the enhancement of propulsion force were more significant. The initial contact phase was closer to the normal range, which implies that the control of ankle dorsiflexion was improved. The plantar FES therapy, the walking speed, single stance phase percentage, double stance phase percentage, step length symmetry index (SI), initial contact phase percentage and start time of the medial/lateral heel were, 0.63±0.3m/s, 23. 16±6.66, 22.03±5.79, 0.15±0.11, 4.16±3.23 and 2.36±6.67/2.38±6.73ms, respectively.